Comparative Study on Value Based Education System in India and USA: Exploring the Impact of Value-based Education on Individual and Societal Development in India and USA (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Advanced education framework is essential for national, social and economic development of the nation. There is a need of significant worth based advanced education framework which empowers youth for self-sustainability by teaching employment skills and thus reducing poverty. India's advanced education framework is the third biggest on the planet. This paper presents examination between the present and the ancient education framework. It features the fundamental structure of ancient education which contributed quality manpower soaking up moral, social and civic qualities to the society. The present education framework is tormented by a few reasons as a result of which the result is getting to be self-centric. This requires a few changes in present education sector which can be implemented from ancient education for overall development of students as an individual.